Integration profile of retroviral vector in gene therapy treated patients is cell-specific according to gene expression and chromatin conformation of target cell - Biasco, Luca; Ambrosi, Alessandro; Pellin, Danilo; Bartholomä, Cynthia C.; Brigida, Immacolata; Roncarolo, Maria Grazia; Di Serio, Clelia; Kalle, Christof von; Schmidt, Manfred; Aiuti, Alessandro (EMBO molecular medicine, 2011)
Abstract The analysis of genomic distribution of retroviral vectors is a powerful tool to monitor ?vector-on-host? effects in gene therapy (GT) trials but also provides crucial information about ?host-on-vector? influences based on the target cell genetic and epigenetic state. We had the unique occasion to compare the insertional profile of the same therapeutic moloney murine leukemia virus (MLV) vector in the context of the adenosine deaminase-severe combined immunodeficiency (ADA-SCID) genetic background in two GT trials based on infusions of transduced mature lymphocytes (peripheral blood lymphocytes, PBL) or a single infusion of haematopoietic stem/progenitor cells (HSC). We found that vector insertions are cell-specific according to the differential expression profile of target cells, favouring, in PBL-GT, genes involved in immune system and T-cell functions/pathways as well as T-cell DNase hypersensitive sites, differently from HSC-GT. Chromatin conformations and histone modifications influenced integration preferences but we discovered that only H3K27me3 was cell-specifically disfavoured, thus representing a key epigenetic determinant of cell-type dependent insertion distribution. Our study shows that MLV vector insertional profile is cell-specific according to the genetic/chromatin state of the target cell both in vitro and in vivo in patients several years after GT. See accompanying Closeup by Baum DOI: http://dx.doi.org/10.1002/emmm.201000110.
Gesehen am 23.03.2022